MODUL MATA KULIAH PUBLIC SPEAKING “POWERFULL PRESENTATION” - Enung Nurhayati (Jurnal Komunikasi, 2025)
Presentation is an essential skill in many fields, whether academic, business, or social, and social. In this competitive era, individuals who are not skilled in presentation will lose and be left out. In business and professional fields, communication skills become a basic competency that supports career development and business success. In the academic field, good communication skills can support academic achievement, while in the social field, presentation skills will support a person's existence in their respective social roles. Given the importance of this skill and the many obstacles most people face in understanding and mastering effective presentation techniques to convey messages well to an audience. I feel the need to share my understanding of the theoretical and technical aspects related to presentation skills so that it can be a solution to communication barriers when making presentations and foster confidence to appear to speak clearly and structured in front of the audience. This module is designed to provide guidance on effective presentation techniques using a variety of approaches, such as the use of attractive visuals, organized material structure, and the appropriate use of body language and voice intonation will be discussed in detail. It is hoped that by understanding and applying these techniques, you will become a better speaker and be able to convey information more effectively. This module is systematically packaged so that it is ready to be learned by any learner to achieve the Public Relations Competencies and Sub- Competencies, namely the Presentation Skills Competency Unit. This module is also a guide to the Public Speaking course as well as a guide to the Public Relations competency training conducted by the Communication Studies program